2020
DOI: 10.1002/bbb.2170
|View full text |Cite
|
Sign up to set email alerts
|

Techno‐economic analysis of sugar production from lignocellulosic biomass with utilization of hemicellulose and lignin for high‐value co‐products

Abstract: Sugar derived from lignocellulosic biomass is an important intermediate product, often used for the production of biofuels and value‐added chemicals. It is therefore essential to understand and reduce the production costs of sugar derived from lignocellulosic biomass. This study evaluates the economic feasibility of a biorefinery producing sugar from lignocellulosic biomass using a combination of autohydrolysis and mechanical refining pretreatment. This biorefinery is self‐sufficient in energy, producing exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Giuliano et al 23 determined the selling price to be US$3.5/kg, and concluded that co-production of ethanol and xylitol was desirable. Ou et al 24 performed TEA of a sugarcane production facility co-producing xylitol and polyols, and determined variation in sugar price with production of xylitol and polyols. For a feedstock processing capacity of 1500 MT/day, the selling price of xylitol was US$2/kg.…”
Section: Techno-economic Analysis Resultsmentioning
confidence: 99%
“…Giuliano et al 23 determined the selling price to be US$3.5/kg, and concluded that co-production of ethanol and xylitol was desirable. Ou et al 24 performed TEA of a sugarcane production facility co-producing xylitol and polyols, and determined variation in sugar price with production of xylitol and polyols. For a feedstock processing capacity of 1500 MT/day, the selling price of xylitol was US$2/kg.…”
Section: Techno-economic Analysis Resultsmentioning
confidence: 99%
“…The expected production cost in the NSM was $0.43/kg (dry sugar mixture) in 2020 US dollar equivalents for the concentrated sugar stream for an expected plant lifetime of 30 years and an internal rate of return of 10%. The cost is conservatively high compared to other analyses of sugar production from lignocellulosic biomass, not only in terms of production cost, but also in terms of capital cost per unit of installed production capacity (Michels, 2014;Moncada et al, 2018;Ou et al, 2021), These are generally higher than the historical sugar spot prices in the last five years, ranging between $0.22-0.50/kg (Macrotrends, 2021).…”
Section: Cost Of and Speed Of Sugar Productionmentioning
confidence: 85%
“…Particularly, in the last five years the researchers have attempted to integrate the developed process modules with the technoeconomics to understand the benefits associated with holistic utilization of all biomass components. For instance, Ou et al (2021) showed that if 1500 tonnes of miscanthus was processed for sugar production per day, the minimum sugar selling price (MSSP) was $446/tonnes. 178 However, when the xylose stream obtained when fed-batch strategy fermentation was adopted.…”
Section: E Coli Strain Was Engineered To Hydrolyse Xylan Fraction Of Hemicellulose By Heterologous Overexpression Of β-mentioning
confidence: 99%
“…For instance, Ou et al (2021) showed that if 1500 tonnes of miscanthus was processed for sugar production per day, the minimum sugar selling price (MSSP) was $446/tonnes. 178 However, when the xylose stream obtained when fed-batch strategy fermentation was adopted. 180 Lately Ranganathan (2020) showed that when glucose derived from rice straw was used for ethanol production, but xylose was kept intact, the cost of ethanol was $0.627/L.…”
Section: E Coli Strain Was Engineered To Hydrolyse Xylan Fraction Of Hemicellulose By Heterologous Overexpression Of β-mentioning
confidence: 99%
See 1 more Smart Citation